Expert by experience involvement in mental health nursing education: The co‐production of standards between Experts by Experience and academics in mental health nursing. Issue 5 (24th February 2020) - Horgan, Aine; Manning, Fionnuala; Donovan, Moira O.; Doody, Rory; Savage, Eileen; Bradley, Stephen K.; Dorrity, Claire; O'Sullivan, Hazel; Goodwin, John; Greaney, Sonya; Biering, Pall; Bjornsson, Einar; et al.
Accessible summary: What is known on the subject: Expert by Experience (EBE) involvement in mental health nursing education has demonstrated benefits, including enhancing understanding of holistic and recovery‐focused practice and enhanced application of interpersonal skills. Structure and support for EBE involvement is lacking; often resulting in inadequate preparation and debriefing and tokenistic involvement. Service user involvement in mental health nursing education should be underpinned by lived experience perspectives. What the paper adds to existing knowledge: An exploration of EBE involvement in nursing education from the perspective of those with lived experience. The development of standards designed to provide structure to better support future EBEs involved in higher education. An exemplar for co‐production of standards between EBE and nurse academics which has applicability for other contexts. What are the implications for practice?: The standards could potentially strengthen EBE involvement in mental health nursing education, enhance their confidence and increase the retention of EBEs by creating an inclusive working culture. By increasing support for EBEs, the benefits to mental health nursing practice are likely to be maximized. Abstract: Introduction: Involving people with lived experience of mental distress in mental health nursing education has gained considerable traction yet broader implementation remains ad hoc and tokenistic. Effective involvement requires curricula be informed by lived experience of service use. Aim: To develop standards to underpin expert by experience involvement in mental health nursing education based on lived experience of service use. Methods: Phase one used qualitative descriptive methods, involving focus groups with service users ( n = 50) from six countries to explore perceptions of service user involvement in mental health nursing education. Phase two utilized these findings through consensus building to co‐produce standards to support Experts by Experience involvement in mental health nursing education. Results: Three themes emerged in Phase one: enablers and barriers, practical and informational support, and emotional and appraisal support. These themes underpinned development of the standards, which reflect nine processes: induction and orientation, external supervision, supportive teamwork, preparation for teaching and assessing, "intervision, " mutual mentorship, pre‐ and post‐debriefing, role clarity and equitable payment. Conclusions: These standards form the framework entitled; Standards for Co‐production of Education (Mental Health Nursing) (SCo‐PE [MHN]). Implications for Practice: The standards aim to support implementation of Expert by Experience roles in mental health nursing education.